Developing School Administrative Staff Competence Through Training and Career Development to Face the Digitalization Era - Dewi, Meilani Alfiansyah; Sobri, Ahmad Yusuf; Nurabadi, Ahmad (Proceedings Series of Educational Studies, 2024)
Developing the competence of school administrative staff is one of the essentials in the digitalization era, therefore schools need to improve the knowledge and skills of school administrative staff through training and career development to meet the needs and keep up with the times so that they can create quality schools. The purpose of this study is to solve problems related to school administrative staff who are still stuttering about technology in the digitalization era. This study uses a qualitative descriptive research method. The technique used in this study is Literature Study by reviewing previous studies through articles or journals. The results of this study are that developing the competence of administrative staff in keeping up with the development of digitalization can be done through consistent training and career development.